Practicality and effectiveness of live worksheets-based math e-modules to improve student numeracy - Asfrianti, Sri Dea; Gusmania, Yesi (Universitas Riau Kepulauan, 2024)
Starting from the lack of students' reasoning level on numerical problems, considering the demands of the times and the independent curriculum where students apply technology and the three indicators of numeracy in learning, there is a need for electronic teaching materials in the form of e-modules based on live worksheets to enhance students' numeracy skills. The purpose of this study was to develop a mathematics E-module based on live worksheets to improve student numeracy that is practical and effective. This research method applies the Instructional Development Institute (IDI) procedural development model which consists of 3 main phases: the define phase, the develop phase, and the evaluate phase. This research is focused on the development phase which covers the practical aspects of the E-module, and the evaluation phase which assesses the effectiveness of the E-module. Meanwhile, the definition phase has been conducted in previous research. The subjects in this study were students of class X PPLG 2 SMK Negeri 7 Batam with a total of 40 students. The instrument used for practicality is using a questionnaire and to see the effectiveness of using an essay test. The practicality test in the teacher response questionnaire was 93% and the student response questionnaire was 86% with a very practical category. E-module effectiveness test based on student post-test results obtained 85% with a very effective category. Thus, the live worksheets-based math E-module to improve student numeracy that has been used is declared practical and effective.